REMOTE SETTING OF Nodipecten nodosus (Linnaeus 1758) LARVAE - Robson Cardoso COSTA; Gilberto Caetano MANZONI; Francisco Carlos da SILVA; Carlos Henrique Araújo de Miranda GOMES; João Paulo Ramos FERREIRA; Claudio Manoel Rodrigues de MELO (Boletim do Instituto de Pesca)
The present study aimed to evaluate the growth and survival of Nodipecten nodosus larvae grown in a remote settlement system. Two forms of transport were tested, one in a humid/wet, environment and one submerged in seawater, with a control treatment maintained at the Laboratory of Marine Mollusks (LMM). After transport treatments, individuals were populated simultaneously inside floating boxes directly at sea and in containers under controlled conditions in the Laboratory of the Experimental Center for Mariculture (CEMAR). No statistical differences were observed in larval survival relative to the method of transport in the different experiments. However, statistical differences were observed in evaluation 1 (EVA1) for the survival and growth of larvae transported in submerged seawater and settled in the laboratory. No statistical difference was observed between the control and either wet/humid or submerged treatments in EVA2. The survival values in the control treatment in EVA3 were higher (p<0.05) in relation to the wet and submerged treatments cultivated in the laboratory. It was not possible to observe the presence of pre-seeds in treatments grown at sea. Is possible to transport larvae for 6 hours of travel to be settled in controlled conditions far from their place of origin.